HUBUNGAN POLA ASUH ORANG TUA DAN KECERDASAN INTERPERSONAL DENGAN PENGUASAAN KOMPETENSI PENGETAHUAN IPS SISWA KELAS IV - Eka Monita Wahyuning Santi; I Gede Margunayasa; Ni Nyoman Kusmariyatni (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2019)
This study aims to determine: (1) a positive and significant relationship between parenting and interpersonal intelligence with mastery of social science competency, (2) a positive and significant relationship between interpersonal intelligence and mastery of social science competency (3) positive and significant relationships jointly parenting parents and interpersonal intelligence with mastery of IPS knowledge competencies. This research is an ex post facto research type of correlation research. The population is 220 fourth grade students at SD Gugus XI Buleleng Subdistrict in 2018/2019 academic year. A sample of 135 students was determined by proportional random sampling method. Hypothesis testing uses simple regression test and multiple regression test. Based on the results of the hypothesis test showed: (1) a positive and significant relationship between parenting style and mastery of social science competency with a correlation of 0.621 (2) a positive and significant relationship between interspersonal intelligence and mastery of social science competency with a correlation of 0.689 (3) positive and significant relationship of parenting and interpersonal intelligence with mastery of social science competency with a correlation of 0.786. This means parents' parenting and interpersonal intelligence affect the mastery of the IPS knowledge competency of grade IV students in SD Gugus XI, Buleleng Subdistrict, 2018/2019 Academic Year.